Quality Control Analysis Using the Seven Tools and Kaizen Methods to Minimize Terminal Defects in the Crimping Process - Arba Al-Bar; Rudi Tjahyono (TALENTA Publisher, 2026)
Product quality control plays a crucial role in maintaining competitiveness in manufacturing industries, particularly in high-volume production processes where minor defects can significantly affect product functionality. This study analyzes quality issues in the crimping process of wiring harness terminals at PT XYZ, where 1,170,016 terminals were produced over an eight-month period, resulting in 1,755 defective units (0.15%). The Seven Tools method including check sheets, histograms, scatter diagrams, control charts, pareto diagrams, fishbone diagrams, and stratification was employed to identify defect types and root causes. The analysis revealed that “too short” defects were the most dominant, accounting for 69.17% of total defects. The p-chart control chart indicated that the defect proportion fluctuated beyond control limits in several periods, signaling process instability. Furthermore, root cause analysis identified five main contributing factors: human, material, method, machine, and environment. Based on these findings, improvement proposals were formulated using the Kaizen approach through the Five-Step Plan and Five-M Checklist, focusing on standardization, training, preventive maintenance, and workplace organization. The proposed improvements are expected to enhance process stability, reduce defect occurrence, and support continuous quality improvement in the crimping process.